2004
DOI: 10.1007/s00415-004-1606-6
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Parkinson?s disease

Abstract: Depression, the most common psychiatric complication in Parkinson's disease (PD), affects 40-50 % of PD patients [1]. However, exact epidemiological data are missing. Rates of depression in PD vary between 4 % and 70 % depending on diagnostic criteria and selection of the study population. Application of structured diagnostic interviews (e. g. SCID, MINI, NPI) in non-selected populations would be desirable. Severity of depression and anxiety appears to correlate with disability and reduced quality of life in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 9 publications
1
58
0
7
Order By: Relevance
“…Some researches showed that most PD patients with depression have a course of PD more than five years and the occurrence of depression was relatively correlated with wearing-off and motor fluctuation [16] . Our findings further supported the notion and demonstrated that depression actually reflected the advancement of PD and sub-depression could be deemed as the prodrome of depression, a notion that is shared by many other scholars [17,18] . Depression is a direct result of the advancing neuro-degenerative process within frontal-subcortical systems when the disease affects the serotoninergic and dopaminergic pathways [19,20] .…”
Section: Discussionsupporting
confidence: 87%
“…Some researches showed that most PD patients with depression have a course of PD more than five years and the occurrence of depression was relatively correlated with wearing-off and motor fluctuation [16] . Our findings further supported the notion and demonstrated that depression actually reflected the advancement of PD and sub-depression could be deemed as the prodrome of depression, a notion that is shared by many other scholars [17,18] . Depression is a direct result of the advancing neuro-degenerative process within frontal-subcortical systems when the disease affects the serotoninergic and dopaminergic pathways [19,20] .…”
Section: Discussionsupporting
confidence: 87%
“…Depression is also one of the most common non-motor symptoms of Parkinson's disease and many participants, in both samples, reported taking adjunct antidepressant medication. There is a lack of controlled studies on antidepressant therapy in Parkinson's' disease and very limited systematic research into the efficacy of dopaminergic medication on depression (Lemke et al 2004). Anxiety symptoms also commonly occur in Parkinson's disease patients and have been associated with fluctuations in medication status (Pandya et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The frequently observed side effects of long-term L-DOPA treatment are the wearing off phenomenon, on-off fluctuations, dyskinesia, and psychosis (Lemke et al 2004;Hui et al 2005). Of these, dyskinesia is the most common complication, for which etiology is very complex and unknown, but stimulation of D 1 and D 2 receptors for DA plays a key role (Nutt 1990).…”
Section: Introductionmentioning
confidence: 98%